Development of system monitoring of laboratory air quality based on hybrid wireless sensor network SIONLAP - Rochmad Fauzi (Labor Dasar dan Sentral Universitas Andalas, 2021)
The research develop a wireless sensor network device as a feature of the SIONLAP application to support the laboratory room air quality monitoring system. Support for this system provides user access rights by the function and organizational structure of the Department of Electrical Engineering, Faculty of Engineering, State University of Malang, the main tasks and functions of the academic community, and laboratory managers. Testing of air quality monitoring system devices uses the black-box type Boundary Value Analysis (BVA) technique. Data changes in temperature and humidity values at each node are recorded, then displayed on the Thingspeak server and the SIONLAP application. The product being developed has several characteristics, at node 1 it has an error value of an average temperature of 0,27% and humidity of 1%. At node 2, the average temperature error value is 0,37% and humidity is 0,73%. Based on the product test values developed for the Luxtron 8000 calibrator, the device developed is feasible to be applied to support improved laboratory management and services.